Benefits And Effectiveness Of Direct Village Fund Cash Assistance To Anticipate The Impact Of The Covid-19 Pandemic In Rempoah Village, Baturraden District - Hapsari, Nandya Indah; Bambang, Bambang; Apriyani, Lita; Alfarisy, Farid (Lingka Ekonomika, 2022)
This research was held in Rempoah Village, Baturraden District. The objectives of this study were (1) to analyze the accuracy of the Village Fund Direct Cash Assistance program in achieving the target and (2) to analyze the policy characteristics of the Village Fund Direct Cash Assistance program in Rempoah Village, Baturraden District (Pro-poor, progressive or regressive), and (3) Analyzing the effectiveness of the Village Fund Direct Cash Assistance Program in Rempoah Village, Baturraden District. The number of respondents consisted of 65 Beneficiary Families. This study uses primary data collected by observation, interviews, and questionnaires. This study uses analytical methods in the form of data proportion techniques, Benefit Incidence Analysis (BIA), and Program Effectiveness. Based on the study results, it can be concluded that: (1) The Village Fund Direct Cash Assistance Program in Rempoah Village is right on target. (2) The Village Fund Direct Cash Assistance Program in Rempoah Village is Pro-Poor, and (3) the Village Fund Cash Direct Assistance Program in Rempoah Village is classified as an effective program.